If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 3 = 6 + -2x + 3 Reorder the terms: 3 + 10x = 6 + -2x + 3 Reorder the terms: 3 + 10x = 6 + 3 + -2x Combine like terms: 6 + 3 = 9 3 + 10x = 9 + -2x Solving 3 + 10x = 9 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 3 + 10x + 2x = 9 + -2x + 2x Combine like terms: 10x + 2x = 12x 3 + 12x = 9 + -2x + 2x Combine like terms: -2x + 2x = 0 3 + 12x = 9 + 0 3 + 12x = 9 Add '-3' to each side of the equation. 3 + -3 + 12x = 9 + -3 Combine like terms: 3 + -3 = 0 0 + 12x = 9 + -3 12x = 9 + -3 Combine like terms: 9 + -3 = 6 12x = 6 Divide each side by '12'. x = 0.5 Simplifying x = 0.5
| n*9+4=58 | | 9m^3-7m^4+8m^2= | | 6x-3*6x+3=57 | | -5x^2=-3x | | -3a^10+9a^5+6a^15= | | .25x^2-2y=5 | | .25h+9=.75h-7 | | 3t^2-5t-2t^4= | | 4x^2-42x-22=0 | | 21x^4+18x^2+36x^3= | | 3x^2+12x+20=8 | | -2x^2-x^2-30x-72=0 | | 8x-23=2x+37 | | (3x+5)(7x^2-2x+1)= | | 5+4x=3x^2 | | -2x^2-12x-18=0 | | 10x^2-50x+40=0 | | (a-4)(6a^2+10a-3)= | | 3x^2=4x+5 | | X^2+2-2lnx=0 | | -5x^2-9x=0 | | 4g-10=4g-4 | | -3+x=-3 | | (p+2)(2p^2-5p+4)= | | X^2-2lnx=-2 | | y=2x^2+20x+51 | | (2m+5)(3m-7)= | | (2h-1)(h-4)= | | 3(2q-5)=36 | | (d+4)(d-3)= | | -t-12=9+7t | | 1(14x-7)=21 |